(untitled) (Eurasian Journal of Philology Science and Education, 2025)
The article discusses pragmatic function of phraseological units in facilitating interaction between writers and readers in the newspaper discourse. Being a captivating field within linguistic investigation, pragmatics explores the relationship between language and the contextual factors of background characteristics. The theoretical base of the research is discussed with particular emphasis on the significant contributions made by scholars in the field of phraseological studies, pragmatics and newspaper discourse – M. Kopylenko, A. Kunin, Teun A. van Dijk, N. Fairclough, and others. The study aims to conduct a comprehensive analysis of newspaper articles published in the major American online editions of newspapers such as The New York Times, The Washington Post, and The Wall Street Journal, drawing on qualitative analysis to explore the contextual and functional aspects of phraseological units in newspaper discourse. To demonstrate the relevance of the information, articles from the last six months (September 2023 to March 2024) of newspapers were selected. K. Hyland’s (2005) model of interactional meta-discourse was adopted for analyzing the pragmatic potential of phraseological units within newspaper discourse. The findings reveal that the pragmatic effectiveness and communicative impact of newspaper articles are significantly enhanced by these lexical elements – they boost the impact of the meaning conveyed, reinforce attitudes of the writer, encourage reader engagement by inviting them to reflect on the problem under discussion. The results can be useful in linguistics and journalistic practice to better utilize phraseological units to achieve specific communicative goals. Key words: phraseological unit, newspaper discourse, pragmatics, idiom, phrasal verb, pragmatic potential, journalism.